Calcitonin inhibits intervertebral disc degeneration by regulating protein kinase C. Issue 15 (21st June 2020) - Ge, Jun; Cheng, Xiaoqiang; Yan, Qi; Wu, Cenhao; Wang, Yingjie; Yu, Hao; Yang, Huilin; Zhou, Feng; Zou, Jun
Abstract: Intervertebral disc degeneration (IVDD) is the most critical factor that causes low back pain. Molecular biotherapy is a fundamental strategy for IVDD treatment. Calcitonin can promote the proliferation of chondrocytes, stimulate the synthesis of matrix and prevent cartilage degeneration. However, its effect and the underlying mechanism for IVDD have not been fully revealed. Chondrogenic specific matrix components' mRNA expression of nucleus pulposus cell (NPC) was determined by qPCR. Protein expression of NPC matrix components and protein kinase C was determined by Western blotting. A rat caudal intervertebral disc degeneration model was established and tested for calcitonin in vivo. IL‐1 induced NPC change via decreasing protein kinase C (PKC)‐ε phosphorylation, while increasing PKC‐δ phosphorylation. Calcitonin treatment could prevent or reverse IL‐1‐induced cellular change on PKC signalling associated with degeneration. The positive effect of calcitonin on IVDD in vivo was verified on a rat caudal model. In summary, this study, for the first time, elucidated the important role of calcitonin in the regulation of matrix components in the nucleus of the intervertebral disc. Calcitonin can delay degeneration of the intervertebral disc nucleus by activating the PKC‐ε pathway and inhibiting the PKC‐δ pathway.